2023
DOI: 10.1038/s42003-022-04382-w
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged microgravity induces reversible and persistent changes on human cerebral connectivity

Abstract: The prospect of continued manned space missions warrants an in-depth understanding of how prolonged microgravity affects the human brain. Functional magnetic resonance imaging (fMRI) can pinpoint changes reflecting adaptive neuroplasticity across time. We acquired resting-state fMRI data of cosmonauts before, shortly after, and eight months after spaceflight as a follow-up to assess global connectivity changes over time. Our results show persisting connectivity decreases in posterior cingulate cortex and thala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 70 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…There have been relatively few studies on the effects of weightlessness on the brain, and yet, decades of observations on space-flown animal models and human astronauts have confirmed that physiology is profoundly impacted by spaceflight 32 34 . Growing evidences show that prolonged exposure to spaceflight and microgravity environment leads to alteration of brain function and structure, as suggested by recent analyses of astronauts’ brain fMRI 10 . Even at a smaller scale, microgravity is known to have a direct effect on cells, such as the modification of their cytoskeleton or changes in their physical properties 3 , 35 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…There have been relatively few studies on the effects of weightlessness on the brain, and yet, decades of observations on space-flown animal models and human astronauts have confirmed that physiology is profoundly impacted by spaceflight 32 34 . Growing evidences show that prolonged exposure to spaceflight and microgravity environment leads to alteration of brain function and structure, as suggested by recent analyses of astronauts’ brain fMRI 10 . Even at a smaller scale, microgravity is known to have a direct effect on cells, such as the modification of their cytoskeleton or changes in their physical properties 3 , 35 .…”
Section: Discussionmentioning
confidence: 95%
“…In the same manner that microgravity modifies blood pressure, it also causes vestibular and ocular structural dysfunction as the fluid shift increases the intracranial and intraocular pressure leading to SANS (Spaceflight-Associated Neuro-ocular Syndrome) 8 , 9 . Extensive studies of astronauts alterations of brain structure has recently been substantiated by fMRI analysis of astronauts evidencing subtle yet significant modification of brain connectome 10 . These phenomena are either linked to microgravity itself, via mechanical unloading, or to the intracranial fluid redistribution, or to space radiation.…”
Section: Introductionmentioning
confidence: 99%
“…There have been relatively few studies on the effects of weightlessness on the brain, and yet decades of observations on space-flown animal models and human astronauts have confirmed that physiology is profoundly impacted by spaceflight [17][18][19]. Growing evidences show that prolonged exposure to spaceflight and microgravity environment leads to alteration of brain function and structure, as suggested by recent analyses of astronauts' brain fMRI [5]. Even at a smaller scale, microgravity is known to have a direct effect on cells, such as themodification of their cytoskeleton or changes in their physical properties [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…From a neurological point of view, medical studies on astronauts also showed that space flights have effects on the brain both on the short term (motion sickness, vestibular dysfunction and Spaceflight-associated neuroocular SANS syndrome) and on the long term (increased risk of brain malignancies, premature ageing, accelerated neurodegeneration) [3,4]. Alteration of brain structure has recently been substantiated by fMRI analysis of astronauts evidencing subtle yet significant modification of brain connectome [5]. These phenomena are either linked to microgravity itself, via mechanical unloading, or to the intracranial fluid redistribution, or to space radiation.…”
Section: Influence Of Microgravity On Spontaneous Calcium Activity Of...mentioning
confidence: 99%
“…During spaceflights, astronauts report mental fatigue, disruptions of neurovestibular system, sleep and circadian rhythms, and difficulty concentrating and maintaining a high level of cognitive performance (Arshad and Ferré, 2023; Gupta et al, 2023; Mhatre et al, 2022; Oluwafemi et al, 2021). MRI investigations have revealed that the brain of astronauts undergoes a variety of changes as a consequence of spaceflight missions including changes in tissue volume and microstructure, cerebrospinal fluid distribution and dynamics, and functional connectivity (Gupta et al, 2023; Jillings et al, 2023; Roy-O’Reilly et al, 2021). Understanding how long-term exposure to reduced-gravity environments may influence the neuro-physiological processes and neuroplasticity, i.e.…”
Section: Introductionmentioning
confidence: 99%